Optimization of temperate extrusion-assisted flaking process conditions for the production of ricebean (Vigna umbellata) flakes. (October 2022) - Bepary, Rejaul Hoque; Wadikar, D.D.; Semwal, A.D.
Abstract: The temperate extrusion-assisted flaking process for the production of ricebean flakes has been optimized by using the response surface methodology. The developed flaking techniques could overcome the non-uniform product quality, loss of thermal sensitive nutrients, and prepare multigrain flakes. The process parameters studied were moisture content (MC: 20–30%), barrel temperature (BT: 40–60 °C), and twin-screw speed (TSS: 340–360 rpm). The quality of ricebean flakes was evaluated in terms of bulk density reduction percentage (BDRP), expansion percentage (EP), flakiness factor, water absorption index (WAI), water solubility index (WSI), degree of gelatinization (DG), and overall acceptability (OAA). The best quality flakes were obtained with optimized conditions of 25% MC of flour, 55 °C BT, and 345 rpm TSS. The quality characteristics of the optimized flakes were as follows- BDRP: 27.11 ± 0.72%, EP: 24.85 ± 0.45%, FF: 1.13 ± 0.04, WAI: 3.59 ± 0.15 g/g, WSI: 27.61 ± 0.22%, DG: 83 ± 0.35%, OAA: 8.5 ± 0.1. Industrial relevance: Conventional flaking technology is a simple process that can be easily scaled up by any skilled individual, but it frequently has limitations such as non-uniform quality; loss of thermo-sensitive nutrients, process efficiency, and so on. The process reported in this present investigation is a temperate extrusion-assisted flaking process that provides better process control, product uniformity, incorporation of multiple flours, and a reduction in the loss of thermo-labile nutrients. The ricebean flakes thus prepared had superior quality. The data generated for flaking process optimization would be quite useful while upscaling the process to industrial-scale production. Industries can use this data for their process optimization and validation in the technology scale-up stage. The temperate extrusion-assisted flaking process can also be used to develop ready-to-eat breakfast cereals by blending bean flour with other cereals/ingredients and multigrain combinations. Highlights: Temperate extrusion-assisted flaking process was optimized to get superior quality flakes. Flakiness factor exhibited positive linear effect and negative quadratic effect with MC OAA of flakes was influenced by MC and BT in curvilinear manner. Extrusion of moisten flour (25%) at 55 °C of BT, 345 rpm of TSS resulted top quality flakes. Flakes prepared using the optimized process had better surface area, BD than that by conventional process.